Polysemous Dajare wordplay in Japanese-language advertisement series titled Santarou: A pragmatic study - Mustaqim, Ilham Hijrah; Sunarni, Nani; Suryadimulya, Agus Suherman (Universitas Dian Nuswantoro, 2023)
Dajare is a type of Japanese wordplay used in humorous contexts. Previous studies have only examined dajare formed through homophonic or semi-homophonic word pairs, while polysemous wordplay is more commonly found in English-language puns. This study seeks to describe dajare based on polysemy found in a series of Japaneselanguage television advertisements titled Santarou produced by Au. This study uses the qualitative-descriptive method to describe polysemous dajare found in the data source. The theory used is Attardo’s (2017) general theory of verbal humor to describe how the dajare creates humor in the advertisements. It can be concluded that polysemous dajare wordplay in the data revolves around the incongruity between the original meaning of a word and its derivation in slang and colloquial language.